Implementation of Good Hygiene Practices for Small Scale Production of Local Food - Siti Syahida Mohd Sukarno (2015)
The hygienic aspect of food premise is very important to ensure safety of food. This study was undertaken to assess the pre- and post-implementation of Good Hygiene Practices (GHP} of selected food premise. The determination of the aerobic plate count (APC), yeast and mould count (YMC), total coliform and Escherichia coli were carried out to reveal the hygienic level of the food. There were differences on microbiological analyses of pre- and post-implementation of GHP. The results showed that the aerobic plate counts (CFU/g) for pre- and post- implementation of GHP were 3.65 + 0.95 CFU/g and 3.58 + 0.88 CFU/g. On the other hand, microbiological analyses of yeast and mould of pre and post-implementation of GHP were 3.47 + 1.15 CFU/g and 3.18 + 1.14 CFU/g. However, total coliform and E.coli have unsatisfactory results in which 100% coliform were detected before GHP implementation where as 86.7% coliform were detected post- implementation of GHP. Besides that, the Good Hygiene Practices survey was carried out. The field observations consisted of demographic, personal hygiene and hygiene of food processing plant. The results of survey showed may yg n hiene practices were not implemented in food premise. important reduce diseases potential and other health risks. GHP can GHP ismportant to food reduce contamination of food from bacteria.